100 ADVENTURES TO HAVE BEFORE YOU GROW UP - McNuff, Anna; Rossiter, Clair (London : Walker Books and Subsidiaries, 2020)
Are you looking for an adventure? Every single adventure in this book is tried-and-tested awesomeness. Each one will inspire you to get outdoors, have fun and try something new.
Keywords: Outdoor recreation -- Juvenile literature; Outdoor recreation; Juvenile works; Juvenile literature